A new design for automatic ball balancer to improve its performance. (December 2015) - Rezaee, Mousa; Fathi, Reza
Abstract: In this paper, a new design for automatic ball balancer (ABB) is introduced. It is shown that this type of automatic ball balancer can prevent increasing the vibrations of the rotor at the speed range below the first critical speed. Moreover, the new type of ABB increases the stable range of the perfect balancing configuration. Increasing the balanced stable range causes the new design of ABB to tolerate a wider range of the system parameters in which the perfect balancing configuration is achieved. To investigate the dynamic behavior of a Jeffcott rotor equipped with the new automatic ball balancer, the nonlinear equations of motion are derived using Lagrange's equations, and the range of the parameters in which the system remains in its perfect balancing configuration is obtained. Comparing the results with those corresponding to the traditional ball balancer indicates that the new system reduces the vibration amplitude at the range below the first critical speed and increases the stable range of the perfect balancing configuration.